The Relationship of Coffee Consumption with Stress Levels on Class of 2020 Medical Students Faculty and The Review According to Islamic Perspective - Mochammad Valdist Deyamantha; Werda Indriarti; Ali Ma'sum (Junior Medical Journal, 2023)
Background : Stress is a psychobiological process, namely the existence of a stimulus that is physically and psychologically threatening, then causes anxiety reactions. At this time, stress has become a serious problem for the world's population. Stress that is too heavy and sustainable if not handled it will be harmful to health. According to data from the World Health Organization (WHO) it is estimated that around 450 million people in the world experience health problems due to stress. The problem of stress has been increasing in various circles lately, especially students during the Covid-19 pandemic because of the burden of online learning/assignments, excessive learning, short working time causing stress on students. The purpose of this study was to determine the relationship between coffee consumption and stress levels in students of the YARSI University Medical Faculty class of 2020 and its review according to Islam Perspective.Methods: This type of research is correlational research. with cross sectional research design. Questionnaires are distributed via google form. This research was conducted on YARSI University Medical Faculty students class of 2020 with a total sample of 141 respondents. Data analysis used the Spearman Rank test.Results: Based on the results of statistical tests, there is no relationship between coffee consumption and stress levels in YARSI University Medical Faculty students class of 2020. With a Sig. 0.397 ? ? (0.05)Conclusion: There is no statistically significant relationship between coffee consumption and stress levels.